Vibration effect analysis of roller dynamic unbalance on the cage of high-speed cylindrical roller bearing. (10th November 2018) - Cui, Yongcun; Deng, Sier; Niu, Rongjun; Chen, Guoding
Abstract: This paper presents a nonlinear dynamic differential equations of high-speed cylindrical roller bearing considering the impact of roller dynamic unbalance. The cage vibration characteristics are investigated as a function of roller dynamic unbalance, structure parameters and working conditions. The fast Fourier transformation, cage orbit and vibration acceleration level are used to evaluate the vibration magnitude of the cage. The results show that: (1) Roller dynamic unbalance can affect the state of the cage motion and cause the cage's vibration acceleration level to increase. Once the roller dynamic unbalance exceeds a threshold, the cage will produce a high frequency vibration; (2) The most significant impact on the cage vibration is roller dynamic unbalance in angular direction of roller axis, followed by radial and axial direction; (3) A smaller radial clearance and a reasonable pocket clearance are beneficial to reducing the effect of roller dynamic unbalance on the cage vibration. It is recommended to take a larger cage-race guide clearance within a certain range to lower the cage vibration; (4) The cage vibration due to the roller dynamic unbalance increases with the bearing speed, and is greater than that of the cage with ideal roller. The effect of roller dynamic unbalance on the vibration of cage under high-speed condition is greater than that of the low-speed condition. The increase of the radial load of the bearing, to a certain extent, can reduce the vibration of cage considering the roller dynamic unbalance.